The Role of Literary Texts in Teaching (On the Example of Modern Literature – Z. Prilepin) - Madinabonu, Akhmedova; Nasiba, Niyazova (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the main factors of the influence of the literary sphere on jurisprudence were considered. The role of literature in the modern world is a rather complicated issue. The fact that literature forms a system of moral values of the reader, no one doubts. It is well known that literature, as a form of verbal art, develops eloquence and enriches a person’s vocabulary. Helping him to improve his speech and developing dynamically in his field of activity. The relevance of the chosen topic is connected with the need to comprehend the influence of modern works in the development of the activity of a lawyer-speaker. Today, modern youth hardly reads the works of writers; they do not want to waste their time on this. They better spend their leisure time on the Internet talking with friends and watching different movies. For students of law schools, the requirements of readiness for orientation in a life saturated with information flows and for continuous self-learning have become mandatory. The use of a communication network in the study of modern literature is the norm today. In this regard, it is of particular importance how the writer wrote his work. In our article, we showed how lawyers need literature for further work. This article also discusses the role of Zakhar Prilepin in the context of modern Russian literature. He writes willingly and openly on topics of concern to the general public. One of the essential components of such statements is his reflections on classical and modern Russian literature, showing love or, on the contrary, dislike for the work of this or that author. The aim of the work is to determine the transformation of modern Russian prose on the example of the works of contemporary Russian writer Zakhar Prilepin. His views on the formation and development of the literary process in the twenty-first century explore the peculiarities of the hero and the specifics of the writer’s artistic world based on the work and literary analyses. And this makes the works of Zakhar Prilepin relevant for law students.